Holon e Heteron: osservazioni per un collegamento fra il "Teeteto" e il "Sofista" - Elisa Magrì (Revista de Filosofia Antiga, 2015)
It is noteworthy that both in the Theaetetus and in the Sophist Plato aporetically introduces the notion of holon. The author argues that it is possible to outline a connection between the two dialogues by focusing on the methodological relevance of holon and heteron. Several hints contained in the Theaetetus suggest that Plato conceives of holon as a method of dialectical thinking, underlying the process of soul’s reasoning. The Theaetetus presents this notion ex negativo due to the lack of distinction between difference (heteron) and negation (not being). By contrast, the Sophist shows that heteron is the read thread guiding the dialectics of forms as well as the communication between the soul and the eidetic sphere. Accordingly, the Sophist entails that the process of soul’s reasoning is correlative to the eidetic horizon in so far as they both rely on a holistic methodology that is activated by the quest for the difference.